What are the latest recommendations for pneumococcal vaccines?. Issue 4 (April 2016) - Fabel, Patricia H.; Horton, Emily C.; Shealy, Kayce
Abstract : ABSTRACT: The Advisory Committee on Immunization Practices recently updated its guidelines on pneumococcal pneumonia vaccines for older adults. The new guidelines recommend that patients age 65 years and older receive the PCV13 vaccine in a series along with the PPSV23 vaccine. This article summarizes these changes along with a review of when to vaccinate other key adult populations.